NEUROPATI PERIFER PADA PEMBERIAN OBAT ANTI TUBERKULOSIS LINI PERTAMA BERDASARKAN PEMERIKSAAN NERVE CONDUCTION STUDY DAN FAKTORFAKTOR YANG MEMENGARUHINYA - Puspasari*, Nizar Yamanie**, Fitri Octaviana**, Joedo Prihartono*** (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION INDONESIA RANKS THIRD IN NUMBER OF TB CASES IN THE WORLD ANTITUBERCULOSIS OAT MUSTBE USED WITHIN A PERIOD LONG ENOUGH SO THAT THE SIDE EFFECTS OF EACH OAT BIG ENOUGH ISONIAZID INH ASTHE MOST IMPORTANT FIRST ORDER ANTITUBERCULOSIS MEDICATION SHOULD BE PRESENT IN ALL TREATMENT REGIMENSPERIPHERAL NEUROPATHY PNP DUE TO DISTURBANCE OF PYRIDOXINE METABOLISM IS ONE OF THE MOST COMMONSIDE EFFECTS OF THIS DRUG EARLY DETECTION OF PERIPHERAL NEUROPATHY IN THE FIRST LINE OF OAT USERS ARE VERYIMPORTANT REQUIRED INITIAL ASSESSMENT IS MORE SENSITIVE THAN CLINICAL FINDINGS TO ASSESS THE OCCURRENCE OFPERIPHERAL NEUROPATHY USING ELECTRONEUROGRAFI ENG WITH THE BEGINNING OF A MORE SENSITIVE ASSESSMENTIS EXPECTED TO BE CARRIED OUT IN ACCORDANCE TO THE PATIENT BENEFIT AS TO PREVENT THE ADVANCED STAGES OFPERIPHERAL NEUROPATHY